Nomenclatural comments on the Rusty-spotted Genet (Carnivora, Viverridae) and designation of a neotype - Gaubert, Philippe; Tranier, Michel; Veron, Geraldine; Kock, Dieter; Dunham, Amy E.; Taylor, Peter J.; Stuart, Chris; Stuart, Tilde; Wozencraft, Chris W. (Zootaxa, 2003)
The first purpose of this paper is to designate a neotype for Genetta maculata (Gray, 1830), a genet belonging to the “tigrina-pardina” complex (family VIVERRIDAE) and lacking a type locality. The main aim is to stabilize the classification for this complex and provide a definitive base for naturalists and field workers. The name G. maculata (Gray, 1830) is currently less in use than G. rubiginosa Pucheran, 1855, but the type specimen of the latter is an individual of another species, G. thierryi Matschie, 1902. The second purpose is therefore to conserve the name G. thierryi Matschie, 1902 following prevailing usage.